Pemahaman Hukum Islam tentang Riba dalam Praktik Jual Beli: Studi Kasus Pedagang Pasar Tradisional - Putri, Ramanitya Dewi; Winario, Mohd (Journal of Legal Sustainability, 2025)
This study aims to analyze the understanding of traditional market traders regarding Islamic law on usury in buying and selling practices and to evaluate the extent to which sharia principles are applied in daily transactions. This study is important considering the rampant practices that contain elements of usury due to the lack of in-depth understanding of religion among small business actors. This study uses a qualitative approach with a case study method conducted on a number of traders in traditional markets. Data collection techniques include observation, in-depth interviews, and documentation. The results of the study indicate that most traders have a limited understanding of the concept of usury according to Islamic law. Some of them still carry out practices that have the potential to contain usury, such as the interest system in capital loans, due to economic needs and the lack of sharia financing alternatives. However, there are also traders who try to avoid usury by choosing a cash buying and selling system or profit-sharing cooperation. This study recommends the need for education and assistance from sharia financial institutions and religious figures so that traders can apply the principles of buying and selling in accordance with Islamic law more optimally.